Rencana Strategis Pengembangan Kompetensi Pemimpin Umat Paroki Yesus Tersalib Balai Sepuak di Keuskupan Sanggau, Kalimantan Barat - Gunung, Philipus; Laksito, Petrus Canisius Edi (Felicitas, 2025)
This research aims to meet the needs of the Crucified Jesus Parish, Balai Sepuak, in improving the competence of Community Leaders. In particular, the Parish of Jesus Crucified Balai Sepuak needs to increase the competence of its Community Leaders in carrying out their pastoral care duties to assist the Parish Pastor, and therefore a Strategic Plan for Developing the Competency of Community Leaders is needed. Therefore, the planning of the National Strategic Plan must focus on things that will be developed to improve the Competence of Community Leaders. The strategic plan and targets are designed using the ADDIE model which stands for Analyzing, Designing, Developing, Implementing and Evaluating. At the needs analysis stage during interviews with the Parish Pastor of Jesus Crucified Balai Sepuak as Rensta user, the Vikjen as an expert, and the Community Leader, it was found that three topics were needed in the Development of Community Leader Competency. This program is designed for five years and covers three areas of development, namely, worship, preaching/teaching and pastoral care. The Strategic Plan has been reviewed by experts consisting of Vijen and the Parish Pastor of Jesus Crucified Balai Sepuak, as well as one of the representatives of the Community Leaders. The content of the Strategic Plan presented is based on its scope, starting from the Vision and Mission to strategic targets. A Strategic Plan was socialized to the Ummah Leaders, and one of the representatives of the Ummah Leaders showed positive comments, especially regarding the Strategic Plan.